Body, self and world : the embodied experience of chronic illness and medical technology - Ní Mháille, Gráinne (Trinity College (Dublin, Ireland). School of Psychology, 2009)
Illness and medical treatment profoundly alter how we experience the body and relate to our worlds. The aim of this thesis is to carry out a conceptual and empirical analysis of the role of the body in the experience of health and medical treatment. Design: 20 (7 men, 13 women) semi-structured interviews were carried out with individuals who had been diagnosed with renal failure or cancer. The technologies of haemodialysis (5), radiation therapy (7) and surgery (8) were investigated. Analysis: The interviews were analysed using a two-step analysis: (i) a thematic analysis that generated themes, which described the participants’ experiences of illness and treatment, was conducted; (ii) an interpretative analysis that generated themes pertaining to the embodied experience of illness and medical treatment. Results: Two overarching motifs were generated in the findings: (i) the impact of illness and medical treatment on the individual in a physical, personal and social sense; (ii) the role of embodied meaning in the experience of illness and medical treatment. Conclusions: Embodied experiences are meaningful. Bodily changes are not experienced objectively: rather they have repercussions for the individual. Conclusions were drawn which suggested practical implications for healthcare as well as theoretical implications about how we can reintroduce the body into psychology.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin